Replication Data for "Subnational Socio-economic Dataset Availability" - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
This is replication data used in the analysis for the correspondence article published at Nature Climate Change: "Subnational socio-economic dataset availability."